Entre a consciência do corpo e o corpo consciente - Pereira, André Rogério (2018)
This research aims to reflect on the process that takes place between the consciousness of the body and the conscious body from the question asked to professional dancers: "Why do you dance?". Considering that this artistic work is intrinsically committed to life beyond the stages and the rehearsal room. Faced with a training that devotes more time to physical development, there is the possibility of reflecting on the overlapping of strategies that approximate the repertoire of life, everyday experiences in the sense of approaching inseparable instances: body and soul. In order to support the idea that body and soul are not dissociated, the research was based on Merleau-Ponty's phenomenology about perception, where by primacy the body is the main way to contact with experience, in the provocations about dance teaching in Brazil, by Klauss Vianna and in the dialogue with other authors, philosophers and thinkers on the artistic and educational experience as Dewey, Larrosa among others. As inspiration of this discussion two personalities in the history of dance: Isadora Duncan and Pina Bausch who revolutionized dance, are fundamental. As a qualitative research methodology of an exploratory nature, interviews were conducted and analyzed with dancers who reinforced the defense that what can not fit into words can only be expressed in dance. Problematizing the teaching of dance with questions related to the prevalence of form, propose overlaps of teaching strategies that favor the approach of students' souls during classes, establishing a possibility of dialogue between the conscious body and the consciousness of the body.